Comparison of Risk Analysis Approaches and a Case Study of the Risk of Incorporating Solar Photovoltaic Systems into a Commercial Electric Power Grid. Issue 1 (24th May 2013) - Chaves, Andrea; Terry Bahill, A.
ABSTRACT This paper compares two common risk‐modeling approaches and then uses them to analyze the risk of incorporating solar photovoltaic (PV) systems into a commercial electric power grid. It uses procedures from both approaches such as Hierarchical Holographic Models, frequency and severity normalization, and avoiding numerical skewing by rare but serious events: It describes the benefits and limitations of these approaches. Then, this paper summarizes the main risks associated with incorporating Solar PV panel systems into a commercial electric power grid, presents a what‐if analysis for extreme scenarios, and explains mitigation strategies to ameliorate these risks. Finally, the paper points out some possible unintended consequences of incorporating Solar PV systems into a commercial electric power grid.